THE PRIORITY NEEDS IN DEVELOPING TEACHER EMPOWERMENT OF KRATHUMBAEN WISETSAMUTTHAKHUN SCHOOL - Thongsima , Sineenart; Jariyarangseeroge, Apiradee (Journal of Educational Review Faculty of Education in MCU, 2026)
This research article aimed to study the current state, desirable state, and priority needs for developing teacher empowerment at Krathumbaen Wisetsamuttakhun School. The study employed a descriptive research method. The research population was Krathumbaen Wisetsamuttakhun School. The informants consisted of 110 administrators and teachers of Krathumbaen Wisetsamuttakhun School in the 2025 academic year. The research instrument was a questionnaire on the current state and desirable state of teacher empowerment development at Krathumbaen Wisetsamuttakhun School. The statistics used for data analysis were frequency, percentage, mean, standard deviation, and the Modified Priority Needs Index (PNImodified). The research findings revealed that the highest priority need for developing teacher empowerment at Krathumbaen Wisetsamuttakhun School was trust and a positive organizational working climate (PNImodified = 0.26), followed by the promotion of leadership and professional roles (PNImodified = 0.18), participation and autonomy in decision-making (PNImodified = 0.18), awareness of personal value, competence, and motivation (PNImodified = 0.16), and professional development and career advancement opportunities, which had the lowest priority need (PNImodified = 0.14). When considering development methods according to the components of teacher empowerment, the findings showed that trust and a positive organizational working climate should be developed primarily through team-based development and a supportive working climate, accounting for 73.64 percent. Participation and autonomy in decision-making should also be developed primarily through team-based development and a supportive working climate, accounting for 56.36 percent. Similarly, the promotion of leadership and professional roles should be developed primarily through team-based development and a supportive working climate, accounting for 56.36 percent. Awareness of personal value, competence, and motivation should be developed primarily through team-based development and a supportive working climate, accounting for 57.27 percent. Meanwhile, professional development and career advancement opportunities should be developed primarily through workshops, accounting for 57.27 percent.